Co-precipitation method for the preparation of ferroelectric CaBi4Ti4O15 - Gaikwad, S. P.; Dhage, S. R.; Ravi, V. (Journal of Materials Science-Materials in Electronics, 2005)
A simple co-precipitation technique has been successfully applied for the preparation of pure single phase CaBi4Ti4O15 (CBT) powders. Ammonium oxalate and ammonium hydroxide were used to precipitate Ca2+, Bi3+ and Ti4+ cations simultaneously. No pyrochlore phase was found while heating powder at 600&DEG; C and pure CBT phase was found to be formed by X-ray diffraction. Particle size and morphology was studied by transmission electron microscopy (TEM). The room temperature dielectric constant at 1 kHz is 400. The ferroelectric hysteresis loop parameters of these samples were also studied. (C) 2005 Springer Science + Business Media, Inc.